ETHNOMATHEMATICS POP-UP BOOK ON GEOMETRY IN TRADITIONAL LAMPUNG HOUSES: Lampung, Indonesia - Pradana, Kenny Candra; Rohani, Anisa; Minadja, Adji W. S. (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to develop an ethnomathematics-based pop-up book as a learning medium, integrating geometric concepts within the context of traditional Lampung houses, to enhance students' conceptual understanding of mathematics and to evaluate the responses of teachers and students as well as the effectiveness of the media. The research employed the Borg & Gall development model with seven steps: data collection, planning, initial draft development, preliminary testing, product revision, main field testing, and dissemination and implementation. Data were analyzed using qualitative and quantitative descriptive methods. Validation results indicated that the media fell into the